PENGARUH BEBAN KERJA, STRES KERJA DAN KONFLIK KERJA TERHADAP KINERJA PEGAWAI DI LEMBAGA PEMASYARAKATAN KELAS IIB KOTA TEBING TINGGI - Marsya Br. Damanik; Mislan Sihite; Rintan Saragih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of workload, work stress, and work conflict on employee performance at the Class IIB Correctional Institution in Tebing Tinggi City. This study uses a quantitative approach with a descriptive method. The population in this study consisted of all 50 employees working as prison guards, who were also used as research samples using a saturated sampling technique. Data were collected through a questionnaire using a Likert scale and analyzed using multiple linear regression analysis with the help of the SPSS program. The results showed that, partially, workload had a significant effect on employee performance, as evidenced by a t-value of 3.323 and a significance value of 0.002 < 0.05. Workstress also had a significant effect on employee performance with a t value of 3.541 and a significance value of 0.001 < 0.05. In addition, work conflict had a positive and significant effect on employee performance with a t-value of 4.404 and a significance value of 0.000 < 0.05. The simultaneous test results show that workload, work stress, and work conflict together have a significant effect on employee performance with a calculated F value of 48.544 and a significance of 0.000 < 0.05. The coefficient of determination (Adjusted R²) value of 0.744 indicates that 74.4% of employee performance is influenced by these three variables, while the rest is influenced by other variables outside the scope of this study.